No Correlation between Blood Benzene Levels and Luteinizing Hormone Plasma Values in Outdoor Workers - Tomei, Francesco; Rosati, Maria V.; Lorusso, Giovanna; Ricci, Lidia; Damato, Felice M.; Caciari, Tiziana; Giubilati, Roberto; Casale, Teodorico; Pimpinella, Bendetta; Marchione, Stefania; Nardone, Nadia; di Luca, Natale M.; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Objective: The purpose of the study is to evaluate whether low-dose exposure to benzene, an environmental pollutant to which male and female traffic policemen are daily exposed to could cause alterations in plasma luteinizing hormone (LH) levels. Methods: From an initial sample of 1594 workers, we only selected 95 workers of whom study we knew the values of late-shift benzene and LH hormone. All subjects underwent biological monitoring (final blood benzene evaluation) and luteinizing hormone dosing. Excluding subjects with the main confounding factors, the final sample included 76 workers. The normal distribution of the variables was evaluated using the Kolmogorov - Smirnov test, followed by the logarithmic transformation of the LH and benzene values. The comparison among means was performed by using the t-test for the independent samples. The ANOVA test was performed for variables with more than 2 modes (ages and seniority) and Pearson correlation index between variables in the total sample and after subdivision as to sex, job, sports activity and smoking. The results were considered significant when p values were less than 0.05. Results / Conclusion: The study did not show a correlation between benzene levels and LH plasma levels in outdoor workers.
Keywords: traffic policemen